Smokers are over-represented in subjects with ahaptoglobinemia in Ghana - Quaye, I.K.; Tagoe, E.A.; Amoah, A.G.; Agbolosu, K.; Aryee, N.A. (Journal of Atherosclerosis and Thrombosis, 2010)
Aim: Smoking has been established as a major risk factor for cardiovascular disease. It causes oxida-tive stress and sub-clinical inflammation, which undermine the antioxidant defense system of the body. We reasoned that natural antioxidant defense systems may be compromised in smokers. To this end, we examined whether haptoglobin (Hp), a potent antioxidant, is impacted negatively by smoking. Methods: Study participants consisted of 121 current smokers and 105 healthy non-smokers without diabetes and without blood smear-positive P. falciparum. Smokers were defined as individuals who smoke at least 1 cigarette a week and are current smokers (occasional and regular). Baseline demographics, hematological indices, lipid profiles, blood pressure, lactate dehydrogenase activity and haptoglobin phenotypes were determined. Results: Ahaptoglobinemia was found to be highly overrepresented in smokers (odds ratio (OR) =3.1, 95% confidence interval (CI)= 1.5-6.5, p=0.002). This observation was not attributed to intravas-cular hemolysis. Hp2-2 phenotype was found to be under represented in smokers (OR=0.53, 95% CI = 0.28-0.99, p = 0.05). Smoking was confirmed to augment hypertension (diastolic blood pressure (DBP) and systolic blood pressure (SBP) in male smokers (p = 0.0001). Interestingly, however, this appeared not to be related to lipid metabolism, as HDL was elevated (p = 0.0007) while LDL was decreased (p= 0.004) in smokers within the study population. Conclusion: We conclude that smoking is a risk factor for ahaptoglobinemia, which will impact negatively on anti-oxidant defenses and augment pro-oxidative stress effects.
Keywords: Ahaptoglobinemia; Antioxidant defense; Smoking